Microfluidic fabrication of imageable and resorbable polyethylene glycol microspheres for catheter embolization. Issue 1 (21st July 2021) - Vogt, Kyle; Aryan, Lavanya; Stealey, Samuel; Hall, Andrew; Pereira, Kieth; Zustiak, Silviya P.
Abstract: Radiopaque and degradable hydrogel microspheres have a range of potential uses in medicine including proper placement of embolic material during occlusion procedures, acting as inherently embolic materials, and serving as drug carriers that can be located after injection. Current methods for creating radiopaque microspheres are either unable to fully and homogeneously incorporate radiopaque material throughout the microspheres for optimal imaging capabilities, do not result in degradable or fully compressible microspheres, or require elaborate, time‐consuming preparation. We used a simple one‐step microfluidic method to fabricate imageable, degradable polyethylene glycol (PEG) microspheres of varying sizes with homogenous dispersion of barium sulfate—a biocompatible, high‐radiopacity contrast agent. The imageability of the microspheres was characterized using optical microscopy and microcomputed tomography as a function of barium sulfate loading. Microspheres with 20% wt/vol barium sulfate had a mean CT attenuation value of 1, 510 HU, similar to that of cortical bone, which should enable visualization with soft tissue. Compared with unloaded microspheres, barium sulfate‐loaded ones saw an increase in gelation and degradation times and storage modulus and decrease in swelling. Imageable microspheres retained compressibility and were injectable via catheter. The developed radiopaque, degradable PEG microspheres have various potential uses for interventional radiologists and imaging laboratories. Abstract :